Heat Transfer Enhancement in a Shell and Tube Heat Exchanger Using Hybrid Nanofluid - Selimefendigil, Fatih; Şenol, Gürel; Öztop, Hakan Fehmi (CRC Press, 2023)
In this chapter, the thermal efficiency of a shell and tube heat exchanger (STHX) is examined by using hybrid nanofluids. The simulation of the system is carried out with the FEM-based code COMSOL Multiphysics 5.5. As the heat transfer fluid, water-based Ag-MgO hybrid nanofluid is used. Besides using a specific nanofluid in the system, baffles are also used in the STHX for further heat transfer enhancement. The effect of Ag-MgO nanoparticles in the system is examined in various cases. The Reynolds number (Re) is taken with a range of 2,500-12,000. The solid volume fraction of the nanofluid (?) is evaluated within the range of 0.01-2%, while inlet temperature of the nanofluid is at 40°C. Depending on the results, when hybrid nanofluid is used in the STHX system, better thermal transport is obtained. When the solid volume concentration of the nanofluid is increased, there has been a remarkable heat transfer enhancement in the system, while there is a 16% rise of heat transfer coefficient at the highest particle loading. The pressure drop is increased substantially as compared to using water as heat transfer fluid. © 2024 selection and editorial matter, Katta Ramesh, Fateh Mebarek-Oudina, and Basma Souayeh; individual chapters, the contributors.